2020
DOI: 10.3389/fpsyt.2020.00751
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction and Related Psychological Factors Among Children and Adolescents in China During the Coronavirus Disease 2019 (COVID-19) Epidemic

Abstract: Background The Coronavirus disease 2019 (COVID-19) is an infectious disease presenting a major threat to public health. This study aims to assess Internet use characteristics and objectively examine the potential psychological factors associated with Internet addiction (IA) during the COVID-19 epidemic. Methods A cross-sectional, anonymized, self-reported survey was conducted among Chinese children and adolescents aged 6 to 18 years old. Participants completed questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
302
2
41

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(378 citation statements)
references
References 34 publications
33
302
2
41
Order By: Relevance
“…Although studies have suggested that experiencing a severe infectious disease epidemic increases the prevalence of mental health issues, [12][13][14][15][16][17][18][19][20][21][22] it is difficult to find relevant literature or empirical studies that explore quarantine hotel employees faced with the challenge of psychological resilience. Therefore, this study aims to investigate the mental health status and psychological impact on quarantine hotel employees during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although studies have suggested that experiencing a severe infectious disease epidemic increases the prevalence of mental health issues, [12][13][14][15][16][17][18][19][20][21][22] it is difficult to find relevant literature or empirical studies that explore quarantine hotel employees faced with the challenge of psychological resilience. Therefore, this study aims to investigate the mental health status and psychological impact on quarantine hotel employees during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Each subscale contains seven items, and is scored using a 4-point Likert scale ranging from 0 (did not apply to me at all) to 3 (much or mostly applied to me). The depression subscale consists of questions 3, 5, 10, 13, 16, 17 and 21, and the score ranges are as follows: normal/no depression (0-9), mild depression (10-13), moderate depression (14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28 and above). The anxiety subscale consists of questions 2, 4, 7, 9, 15, 19, and 20, and the score ranges are as follows: normal/no anxiety (0-7), mild anxiety (8)(9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety (20 and above).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, parents' and teachers' frequent, open, and positive communication patterns with children can prevent children from engaging in addictive behaviors [79]. As the recent COVID-19 pandemic has made children more dependent on the Internet in their daily lives, parents and teachers are suggested to involve children in more offline activities such as physical exercise to decrease their Internet use [4].…”
Section: Discussionmentioning
confidence: 99%
“…These statistics imply that Internet use has become essential specifically among the adolescent population. The recent COVID-19 pandemic and the preventive measures (e.g., suspensions of face-to-face classes, lockdown of shops and restaurants) has led to increased use of the Internet in the daily lives of children [4]. Therefore, Internet addiction has become an increasingly important public health issue worldwide.…”
Section: Internet Use Among Childrenmentioning
confidence: 99%